PERANCANGAN SISTEM REPOSITORY JOINT INSPECTION PADA PT. KAI (PERSERO) REGIONAL III PALEMBANG - Misinem - Misinem; Tri Basuki Kurniawan; Rika Nuraini (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
PT. Indonesian Railways Regional Division III is still processing and storing reports manually. The best system was developed called the website-based Repository Joint Inspection System, aiming to make it easier for employees to manage, store, and monitor existing reports for the managerial. This system was developed using the RUP (Rational Unified Process) method. This system has four types of users, Admin, User, Manager, and Safety. However, this study will explore and explain the upload, download, and delete processes of file features in more detail. Testing on this system uses the black box method with feature test techniques. Based on the test results, the system developed in this study follows the expected results, so it can be concluded that this system is suitable for managing and storing reports.